2018
DOI: 10.1029/2017ja025038
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Energetic Particle Precipitation on Mesospheric OH – Variability of the Sources and the Background Atmosphere

Abstract: Using a new analysis technique, we estimate the precipitating particle fluxes measured by the Medium Energy Proton and Electron Detector on the National Oceanic and Atmospheric Administration Polar Orbiting Environmental Satellites. These fluxes are used to quantify the direct impact of energetic particle precipitation (EPP) on mesospheric hydroxyl (OH) measured from the Aura satellite during 2005–2009 in the Northern Hemisphere, covering the declining and minimum phase of solar cycle 23. Using multiple linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…High temperatures imply reduced production of O 3 based on photochemistry. Zawedde et al () show that SPEs contribute approximately 13% to the OH variability at 75 km within geomagnetic latitudes 55°–70°N (auroral zone) for years 2005 to 2009. In the same Figures and , there is no clear one‐to‐one relation between the EEP‐induced OH and the O 3 reduction as reduction seems to be in phase with the regions rich in H 2 O, more evident in Figure .…”
Section: When and Where Is Eep Important For The Tertiary O3 Maximum?mentioning
confidence: 99%
See 1 more Smart Citation
“…High temperatures imply reduced production of O 3 based on photochemistry. Zawedde et al () show that SPEs contribute approximately 13% to the OH variability at 75 km within geomagnetic latitudes 55°–70°N (auroral zone) for years 2005 to 2009. In the same Figures and , there is no clear one‐to‐one relation between the EEP‐induced OH and the O 3 reduction as reduction seems to be in phase with the regions rich in H 2 O, more evident in Figure .…”
Section: When and Where Is Eep Important For The Tertiary O3 Maximum?mentioning
confidence: 99%
“…With the availability of OH and O 3 observations from Aura microwave limb sounder (MLS), several studies have confirmed the SPE-HO X link to mesospheric O 3 depletion (e.g., Damiani et al, 2008;Seppälä et al, 2006;Sofieva et al, 2009;Verkhoglyadova et al, 2015Verkhoglyadova et al, , 2016. With the Aura MLS, a number of studies have also confirmed the importance of EEP on OH (e.g., Andersson et al, 2012Andersson et al, , 2014bVerronen et al, 2011;Zawedde et al, 2016Zawedde et al, , 2018. The impact of EEP on O 3 is, however, typically investigated without simultaneous OH measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, near-infrared D. A. Newnham et al: Simulation study for ground-based Ku-band microwave observations 1377 and visible airglow emissions in the X 2 ro-vibrational Meinel system are due to deactivation of vibrationally excited OH * (v = 7 to v = 9) generated by the highly exothermic reaction of atomic hydrogen with O 3 . Satellite measurements of Meinel band nightglow have shown that OH * occurs in a ∼ 8 km thick layer near 90 km (Zhang and Shepherd, 1999). Ground-based spectroscopic measurements of individual OH vibrational bands in the Meinel emissions can be used to infer temperatures at the mesopause region and estimate relative populations of the v states (e.g.…”
Section: Previous Mesospheric Ozone and Hydroxyl Measurementsmentioning
confidence: 99%
“…In contrast, near-infrared and visible airglow emissions in the X 2 ro-vibrational Meinel system are due to deactivation of vibrationally excited OH * (v = 7 to v = 9) generated by the highly exothermic reaction of atomic hydrogen with O 3 . Satellite measurements of Meinel band nightglow have shown that OH * occurs in a ∼ 8 km thick layer near 90 km (Zhang and Shepherd, 1999). Ground-based spectroscopic measurements of individual OH vibrational bands in the Meinel emissions can be used to infer temperatures at the mesopause region and estimate relative populations of the v states (e.g.…”
Section: Previous Mesospheric Ozone and Hydroxyl Measurementsmentioning
confidence: 99%